(untitled) (Research, Society and Development, 2021)
The theme overweight and obesity related to quality of life (QoL) is a matter of great relevance to humanity, as they propose to rescue the value of people affected by these pathologies, as well as their implications for the QdL of these individuals. This subject can provide motivating actions, psychic and physical strength of the subjects, which refers to the behavior of individuals for a better performance of social and organizational activities. From this perspective, this study aimed to identify the perception of the effects on federal public servants regarding their participation in the Project to Combat Overweight and Obesity. It was field research, which, at first, was characterized as qualitative and documentary and, at a second moment, as quantitative, descriptive and correlational. For data collection, two instruments were used: Questionnaire, with the sociodemographic characterization and the perception of the project, and the SF-36, which were applied to 20 participating civil servants. Data analysis was performed using Bardin Content Analysis and SPSSWIN statistical package, in its version 24.0, to tabulate the data and perform descriptive statistical analyzes. The results revealed that in the qualitative aspect, despite the proposals of the project of QdL being for the improvement of the life of its participants.